Tumor-Associated Microbiota in Esophageal Squamous Cell Carcinoma - Yang, Weixiong; Chen, Chang-Han; Jia, Minghan; Xing, Xiangbin; Gao, Lu; Tsai, Hsin-Ting; Zhang, Zhanfei; Liu, Zhenguo; Zeng, Bo; Yeung, Sai-Ching Jim; Lee, Mong-Hong; Cheng, Chao (Frontiers in Cell and Developmental Biology, 2021)
Important evidence indicates the microbiota plays a key role in esophageal squamous cell carcinoma (ESCC). The esophageal microbiota was prospectively investigated in 18 patients with ESCC and 11 patients with physiological normal (PN) esophagus by 16S rRNA gene profiling, using next-generation sequencing. The microbiota composition in tumor tissues of ESCC patients were significantly different from that of patients with PN tissues. The ESCC microbiota was characterized by reduced microbial diversity, by decreased abundance of Bacteroidetes, Fusobacteria and Spirochactes. Employing these taxa into a microbial dysbiosis index demonstrated that dysbiosis microbiota had good capacity to discriminate between ESCC and PN esophagus. Functional analysis characterized that ESCC microbiota had altered nitrate reductase and nitrite reductase functions compared with PN group. These results suggest that specific microbes and the microbiota may drive or mitigate ESCC carcinogenesis, and this study will facilitate assigning causal roles in ESCC development to certain microbes and microbiota.